A flume experiment on wood storage and remobilization in braided river systems. Issue 6 (28th February 2014) - Bertoldi, Walter; Welber, Matilde; Mao, Luca; Zanella, Sandra; Comiti, Francesco
ABSTRACT This work investigates wood dynamics in braided streams through physical modelling in a mobile bed laboratory flume, with the specific objective to characterize wood storage and turnover as a function of wood input rate and of wood element type. Three parallel channels (1.7 m wide, 10 m long) filled with uniform sand were used to reproduce braided networks with constant water discharge and sediment feeding. Wood dowels with and without simplified root wads were regularly added at the upstream end of each flume at different input rates, with a 1:2:3 ratio between the three flumes. Temporal evolution of wood deposition patterns and remobilization rates were monitored by a series of vertical images that permitted the recognition of individual logs. Results show that wood tends to disperse in generally small accumulations (< 5 logs), with higher spatial density on top of sediment bars, and is frequently remobilized due to the intense morphological changes. The amount of wood stored in the channel depends on log input rate through a non‐linear relationship, and input rates exceeding approximately 100 logs/hour determine a sharp change in wood dynamics, with higher storage volume and augmented formation of large jams (> 10 elements) that are less prone to remobilization. Presence of root wads seems to play a minor role in wood deposition, but it reduces the average travel distance of logs. Turnover rates of logs were similar in the three flumes, independently of wood input rate and largely resembling the turnover rate of exposed bars. For the simulated conditions, significant effects of wood on bed morphology were not observed, suggesting that interactions with fine sediments and living vegetation are crucial to form large, stable wood jams able to bring about relevant morphological changes. Copyright © 2014 John Wiley & Sons, Ltd.